From Bench to Bedside: Eupatilin Activates Antioxidant Defenses and Reduces Fibrosis in Experimental Cholestasis - Wang, Wei-Lu; Chen, Yan; Tam, Paul Kwong Hang (European Journal of Pediatric Surgery, 2025)
The aim of this study is to explore the protective effects and mechanisms of Eupatilin, a peroxisome proliferator-activated receptor α (PPARα) agonist, on cholestatic liver disease induced by common bile duct ligation (BDL) in mice.We selected Balb/c mice (both male and female) aged 6 to 8 weeks for the common BDL procedure (ethical approval number: MUST-FDCT-20241114001). The groups include the BDL group and the BDL+ Eupatilin group, with three mice in each group. Once the mice developed jaundice postsurgery (5 days), they were treated with Eupatilin via gavage at a dosage of 20 mg/kg daily for a period of 8 days. On day 13, ocular blood was collected, and liver tissues were extracted for histopathological examination with H&E staining, Sirius Red staining, and subsequent RNA sequencing. Statistical differences among the parameters were evaluated using a t-test.Eupatilin reduces the liver weight/body weight ratio by 41% and ameliorates liver necrosis and fibrosis in Balb/c mice. It could decrease alanine transaminase ( p = 0.0498), aspartate aminotransferase (p = 0.0077), while maintaining ALB (Albumin) and γ-GT (gamma-glutamyl transferase) within normal ranges. RNA sequencing analysis revealed that antioxidant genes (acetaldehyde dehydrogenase 2 [Aldh2] and superoxide dismutase 1 [Sod1]) might be the targets of Eupatilin action.We found that Eupatilin can upregulate antioxidant genes (Aldh2; p = 0.0107) and Sod1 (p = 0.0208) of Balb/c mice, thereby ameliorating BDL damage in mice with cholestatic liver disease.
Keywords: Eupatilin; bile duct ligation; antioxidant; cholestatic liver disease